Formation of the Operational-actionable Component of the Future Physical Rehabilitation Specialists' Readiness to Health Protection Activity - Nataliia Bielikova; Svitlana Indyka (Lesya Ukrainka Volyn National University, 2016)
In the article it investigates the operational-actionable component of the future physical rehabilitation specialists' readiness to health protection activity. It is analyzed the practitioner-oriented approach to the formation of the projective-constructive, performing and analytical-reflexive students' skills. It is shown the peculiarities of the active-actionable phase of the training of future specialists in physical rehabilitation to health protection activity. It is stressed the necessity of the application of pedagogical forms and methods of the interactive direction in the process of teaching professionally oriented disciplines, health protection kind of practical training of future specialists in physical rehabilitation. It is experimentally proved the effectiveness of the implementation of the active-actionable phase in the training of the future specialists in physical rehabilitation, that greatly increases their readiness to health protection activity.